The Risk of Non-Communicable Diseases after being Exposed to the Urban Flood; A Literature Review and Meta-Analysis - Renny Nurhasana; Risky Kusuma Hartono (Faculty of Geography, Universitas Gadjah Mada, 2021)
Background: Risk mapping for the various types of non-communicable diseases (NCDs), which lead to the cause of death due to the impact of the urban flood, is rarely conducted. The study aimed to conduct a Systematic Literature Review (SLR) and meta-analysis of the risk of various NCDs after the community experienced the urban flood disaster. Methods: The data was taken from PubMed, ScienceDirect, Taylor and Francis, and ProQuest from June 2010 to June 2020 by searching for the words of flood and NCDs that only occurred in urban areas. This study refers to the guideline that is widely used to conduct meta-analysis research, namely PRISMA. The procedure was started by searching, screening, and validating the original articles through meta-analysis using R Studio. Result: Twenty-six original articles were selected for SLR, and only two articles were not eligible for meta-analysis. Mental illness (0.53, 95% CI, 0.33-0.68), heart problems (0.39, 95% CI -0.11-0.73), and respiratory problems (0.53, 95% CI, 0.02-0.82) are the NCDs categories occurring after the community, predominantly female and the community aged >40 years, was exposed to the urban flood. This risk magnitude finding complements the previous studies that only did a literature review. The heterogeneous result (tau^2 p-value>0.05) and bias effects of publication (Egger test p-value>0.05) indicated that immediate assistance for victims is essential to prevent the onset of NCDs. Conclusion: Without early prevention and urban planning, the urban flood disaster can contribute to mental illness, heart problems, and respiratory problems.